Assessing audit committee effectiveness of a government statutory body: a case study of the Inland Revenue Board of Malaysia - Sheikh Hassan, Ahmad Fahmi; Mamat, Adi Fazuli; Karbhari, Yusuf; Mohamad, Muslim Har Sani (Universiti Putra Malaysia, 2018)
This study examines the effectiveness of an Audit Committee (AC) operating in a large government statutory body in an emerging economy, namely the Inland Revenue Board of Malaysia (IRBM). This study is timely, as previous studies focussing on AC effectiveness in relation to the public sector are sparse. Data collection was through in-depth interviews with key individuals involved in the IRBM governance process, including AC members, senior management and external auditors. The study finds existence of a weak AC governance function that inadequately oversees financial reporting and internal control systems. We find the independence of AC members questionable, as a communication gap exists between AC members and the external auditor. In particular, the study highlights that top management should ensure that its AC fulfils its assigned role and that urgent attention is given to issues on composition, appointment and diligence of its AC members. We conclude that the IRBM should consider improving independence by appointing an external independent AC member(s) from either the big four or an influential industry expert to provide the necessary input and expertise to ensure that public confidence continues.